2022
DOI: 10.1038/s41598-022-22991-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization method and experimental research on attitude adjustment scheme of attitude adaptive rescue robot

Abstract: To improve the space attitude adjustment efficiency of the robot designed in this study, the average water level height variation of each ballast tank during the rescue process and the ballast water filling mass before the rescue process are taken as optimization variables, the minimal ballasting time during rescue process as the optimisation objective, and the heel and trim inclination angle, and stability in the rescue process as the constraint conditions. For the first time, an optimization method of a resc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Topalov et al [5] developed an information system for the real-time acquisition of the operational parameters of the ballast system, and the research results confirmed the effectiveness of this information system for realizing the automatic allocation of ballast water. Wang et al [6] proposed an optimization method based on the dynamic programming algorithm for the ballast process of underwater rescue robots, established and solved the optimization model with the minimum ballast time as the optimization objective, and verified the feasibility of the optimization results by using the simulation results. Adi et al [7] divided the lifting processes into several stages and employed a multi-objective evolutionary algorithm to determine the optimal ballast-allocation scheme for each stage, with numerical simulation results finding that the obtained allocation scheme can significantly improve the ballast efficiency compared with traditional approaches.…”
Section: Crane Ballast Systemmentioning
confidence: 99%
“…Topalov et al [5] developed an information system for the real-time acquisition of the operational parameters of the ballast system, and the research results confirmed the effectiveness of this information system for realizing the automatic allocation of ballast water. Wang et al [6] proposed an optimization method based on the dynamic programming algorithm for the ballast process of underwater rescue robots, established and solved the optimization model with the minimum ballast time as the optimization objective, and verified the feasibility of the optimization results by using the simulation results. Adi et al [7] divided the lifting processes into several stages and employed a multi-objective evolutionary algorithm to determine the optimal ballast-allocation scheme for each stage, with numerical simulation results finding that the obtained allocation scheme can significantly improve the ballast efficiency compared with traditional approaches.…”
Section: Crane Ballast Systemmentioning
confidence: 99%